2013
DOI: 10.1016/j.foodcont.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

First detection of paralytic shellfish poisoning (PSP) toxins in Icelandic mussels (Mytilus edulis): Links to causative phytoplankton species

Abstract: 17Paralytic shellfish poisoning (PSP) toxins were detected in blue mussels (Mytilus 18 edulis) from two harvesting areas, Eyjafjordur on the north coast and Breidafjordur on 19 the west coast of Iceland in 2009. During a bloom of Alexandrium spp. at both 20 locations in June of that year, blue mussels were found to be contaminated with 21 paralytic shellfish toxins (PSTs), leading to extensive closures of these harvesting 22 sites. 23Phytoplankton data taken during this time showed the presence of large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In contrast, water column temperatures measured in Iceland were much higher, ranging from 2 to 12 °C in Arnarfjörđur and 6 to 15 °C in Breiđafjörđur; with the exception of the deepest areas of Arnarfjörđur (>60 m), water temperatures were generally >8 °C. Notably, Burrell et al (2013) observed high cell concentrations (>10,000 cells L −1 ) of Alexandrium spp., which they tentatively designated as A. tamarense along with small numbers of A. ostenfeldii , in Breiđafjörđur and in Eyjafjordur (northern Iceland) in 2009. Low to moderate Alexandrium spp.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, water column temperatures measured in Iceland were much higher, ranging from 2 to 12 °C in Arnarfjörđur and 6 to 15 °C in Breiđafjörđur; with the exception of the deepest areas of Arnarfjörđur (>60 m), water temperatures were generally >8 °C. Notably, Burrell et al (2013) observed high cell concentrations (>10,000 cells L −1 ) of Alexandrium spp., which they tentatively designated as A. tamarense along with small numbers of A. ostenfeldii , in Breiđafjörđur and in Eyjafjordur (northern Iceland) in 2009. Low to moderate Alexandrium spp.…”
Section: Discussionmentioning
confidence: 93%
“…PSP toxins in blue mussels were recently reported for the first time from Iceland, along with record high numbers of toxic Alexandrium spp. (>16,000 cells L −1 ) (Burrell et al 2013). Additionally, PSP toxins were detected in scallops at levels exceeding regulatory limits for the first time in western Greenland (Baggesen et al 2012), and A. fundyense was isolated and identified from nearby waters.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not this ribotype/species dominates throughout the Arctic remains an open question, largely due to the lack of molecular evidence. For example, the toxigenic natural populations of the Alexandrium tamarense complex found in Icelandic fjords were assigned to A. tamarense based upon microscopic observation of cells by the Utermö hl method, but no molecular data on ribotyping were provided (Burrell et al, 2013). Confirmation of the presence or absence of alternative ribotypes of this species complex in the Arctic might be more comprehensively investigated by additional screenings of planktonic cells by various molecular probe-based methods, such as in situ hybridization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This general pattern is also consistent within A. tamarense Group I ribotype strains from the western Arctic (Chukchi Sea), where the N-sulfocarbamoyl toxin C2 dominated, followed by STX and GTX2/ 3, with lesser amounts of GTX1/4 and NEO in decreasing relative molar ratios (Gu et al, 2013b). In contrast, natural populations of the A. tamarense group in Icelandic fjords yielded dominance by the carbamoyl toxins, with GTX2/3 > STX > GTX1/4 in decreasing order of relative abundance, and the absence of N-sulfocarbamoyl toxins and NEO (Burrell et al, 2013). Populations from highly diverse locations along the eastern Russian coast, including Arcticadjacent waters of the Bering Sea, were highly variable in toxin profile, but consistently contained significant (often dominant) proportions of N-sulfocarbamoyl toxins, particularly C2 or B1 (=GTX5) (Orlova et al, 2007).…”
Section: Psp Toxinsmentioning
confidence: 99%
See 1 more Smart Citation